The influence of metformin on IGF-1 levels in humans: A systematic review and meta-analysis. (January 2020) - Yang, Xiaodong; Kord-Varkaneh, Hamed; Talaei, Sam; Clark, Cain C.T.; Zanghelini, Fernando; Tan, Shing Cheng; Zarezadeh, Meysam; Mousavi, Seyed Mohammad; Rahmani, Jamal; Zhang, Yong
Graphical abstract: Abstract: Background: A meta-analysis is needed to comprehensively consolidate findings from the influence of metformin on IGF-1 levels. The present study was conducted with the objective to accurately evaluate the influence of metformin intake on IGF-1 levels via a meta-analysis of randomized controlled trials. Methods: A comprehensive systematic search was carried out in PubMed/MEDLINE, Web of Science, SCOPUS and Embase from inception until June 2019. Weighted mean difference (WMD) with the 95 % CI were applied for estimating the effects of metformin on serum IGF-1 levels. Results: 11 studies involving a total of 569 individuals reported changes in IGF-1 plasma concentrations as an outcome measure. Pooled results demonstrated an overall non-significant decline in IGF-1 following metformin intake (WMD: -8.292 ng/ml, 95 % CI: -20.248, 3.664, p = 0.174) with heterogeneity among (p = 0.000, I 2 = 87.1 %). The subgroup analyses displayed that intervention duration <12 weeks on children (WMD:-55.402 ng/ml, 95 % CI: -79.845, -30.960, I2 = 0.0 %) significantly reduced IGF-1. Moreover, in age 18 < years older metformin intake (WMD: 15.125 ng/ml, 95 % CI: 5.522, 24.729, I2 = 92.5 %) significantly increased IGF-1 than 18 ≤ years older (WMD:-1.038 ng/ml, 95 % CI: -3.578, 1.502, I 2 = 78.0 %). Following dose-response evaluation, metformin intake reduced IGF-1 (coefficient for dose-response analysis= -13.14, P = 0.041 and coefficient for liner analysis= -0.066, P = 0.038) significantly based on treatment duration. Conclusion: We found in children, intervention duration <12 weeks yielded significant reductions in IGF-1, whilst paradoxically, in participants >18 years old, metformin intake significantly increased IGF-1. We suggest that caution be taken when interpreting the findings of this review, particularly given the discordant supplementation practices between children and adults.